Some Aggregate Measures of Population Distribution of Nepal - Sharma, Pitambar; Gewali, Laxmi Prasad (Himalayan Review, 2011)
Not available. Key words: Population distribution; Physiographic density; Nepal The Himalayan Review Vol. 15, 1983-18984 Page: 1-10 Uploaded Date: April 13, 2011